Infection patterns of Nile tilapia (Oreochromis niloticus L.) by two helminth species with contrasting life styles - Akoll, Peter; Konecny, Robert; Mwanja, Wilson W.; Schiemer, Fritz (Parasitology research, 2012)
The larval stages of Bolbophorus sp. (digenean) and Amirthalingamia macracantha (cestode) are frequently reported in Oreochromis niloticus in Uganda. Little, however, is known about their infection patterns. This study examined the influence of habitat type, host size, and sex and weather patterns on the parasite populations in Uganda. A total of 650 fish were collected between January and November 2008 from a reservoir, cages, fishponds and a stream. The prevalence and intensity of A. macracantha and the prevalence of Bolbophorus sp. differed across the water bodies reflecting the effect of habitat characteristics on parasite transmission. Host sex did not significantly influence the infection patterns, although female fish were slightly more parasitized than male and sexually undifferentiated individuals. The fish size was positively correlated with helminth infections demonstrating accumulation and prolonged exposure of larger (older) fish to the parasites. The metacercariae population did not vary significantly across months, while monthly A. macracantha infection fluctuated markedly. With regard to rain seasons, higher prevalence and intensity of A. macracantha were recorded in wet season. For Bolbophorus sp., only the prevalence varied with seasons, with higher prevalence recorded in the dry season than in wet season. Generally, Bolbophorus sp. responded weakly to changes in water body, host sex and size and weather patterns. Rainfall appears to be an essential cue for coracidia hatching.
Keywords: Infection patterns; Nile tilapia (Oreochromis niloticus L.); Helminth species; Life styles